Effects of digital devices usage in children - Chandran, Vidhya; Gopinath Menon, Meena; Thulasidas, Mithun; Molkere, Vivek (International Journal Of Community Medicine And Public Health, 2025)
Background: Aim of study was to assess the impact of digital device use on ocular parameters in children. Methods: A cross-sectional study was carried out wherein patients were grouped depending on the duration of use and the break in between the usage of digital devices. The impact of screen time and break time were correlated with symptoms of digital eye strain and various orthoptic abnormalities in these children. Results: A total of 127 children were enrolled in the study. Most of the children had a screen time exposure of 4-6 hours (41.6%), while the most common finding in respect to orthoptic abnormality was fusional vergence dysfunction (33.9%). The common symptoms in children were headache (91.3%) and eye pain (61.4%). Most of the children took a break time of <10 minutes in an hour (69.3%). Mobile-based devices were associated with fusional vergence dysfunction and accommodative excess (AE) (p<0.001). The association between the break time and orthoptic dysfunction was statistically significant (p=0.001). Conclusions: Increased screen time and reduced break time between screen usage in our study have been correlated with an increased incidence of orthoptic abnormalities and symptoms related to digital eye strain.